A polyester fiber yarn and a method for manufacturing the same
By preparing moisture-absorbing and antistatic modifiers for polyester fibers and utilizing the synergistic effect of nano-zinc oxide and oleamide, the problems of poor moisture absorption and easy accumulation of static electricity in polyester fibers were solved, thereby achieving improved high-efficiency moisture absorption and antistatic properties of polyester fibers.
Patent Information
- Application Number
- CN202610486698.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-14
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-04-14
AI Technical Summary
Polyester fibers have poor moisture absorption and are prone to static electricity accumulation. Existing methods for improving them are mutually interfering and it is difficult to improve both moisture absorption and antistatic properties at the same time.
A hygroscopic modifier was prepared by acid activation and silane modification of bentonite followed by grafting with chitosan; an antistatic modifier with a core-shell structure was formed by oxidizing and polymerizing conductive carbon black, and nano zinc oxide and oleamide were introduced as interface coordinating components to ensure uniform dispersion of the two modifiers in the PET matrix.
It significantly improves the moisture absorption and antistatic properties of polyester fibers, avoids heterogeneous agglomeration, and forms a highly efficient conductive network.
Smart Images

Figure CN122235859B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-performance polyester fiber technology, belonging to patent classification number D01F6 / 92, specifically to a polyester fiber yarn and its preparation method. Background Technology
[0002] Polyester fiber is a synthetic fiber made primarily from polyethylene terephthalate (PET) through melt spinning. Due to its excellent mechanical properties, weather resistance, and processability, it is widely used in clothing, home textiles, and industrial textiles. However, polyester fiber molecules lack hydrophilic groups, resulting in a moisture regain of only about 0.4%, extremely poor moisture absorption, and a tendency to cause stuffiness and discomfort when worn. Furthermore, polyester fiber has a high volume resistivity of 10⁻⁶. 14 With a charge on the order of Ω·cm, polyester fibers easily accumulate static charge during friction, leading to problems such as fabric clinging to the skin, dust attraction, and stinging sensation from electrical discharge, severely impacting the wearing comfort and safety of polyester products. Existing technologies for improving the moisture absorption properties of polyester fibers mainly include blending modification and finishing methods. Blending modification improves the fiber's moisture absorption capacity by adding hydrophilic fillers during spinning; however, simple hydrophilic fillers often have poor compatibility with the PET matrix and tend to agglomerate within the fiber, resulting in a decline in its mechanical properties. Methods for improving the antistatic properties of polyester fibers typically involve adding conductive fillers or antistatic agents, such as conductive carbon black, carbon nanotubes, and metal oxides. However, these conductive fillers are difficult to form a uniform and continuous conductive network within the PET matrix, resulting in less than ideal antistatic effects.
[0003] In addition, when simultaneously improving the moisture absorption and antistatic properties of polyester fibers, there is often a problem of mutual interference between the two. That is, the large number of hydrophilic groups (such as hydroxyl, carboxyl, carboxymethyl, etc.) introduced to improve the moisture absorption properties are highly polar. During the melt blending process, they are prone to strong hydrogen bonding with the polar groups on the surface of the antistatic conductive filler. This leads to heterogeneous agglomeration of the moisture-absorbing filler and the antistatic filler. On the one hand, this destroys the ability of the conductive filler to form a continuous conductive path in the matrix, which greatly reduces the antistatic properties. On the other hand, it also blocks the pore structure of the moisture-absorbing filler, reducing the moisture absorption effect. Summary of the Invention
[0004] The purpose of this invention is to provide a polyester fiber yarn and a method for preparing the same, so as to solve the technical problems mentioned in the background art.
[0005] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing polyester fiber yarn includes the following steps: (1) Sodium-based bentonite was acid-activated with hydrochloric acid solution, and then modified with γ-glycidoxypropyltrimethoxysilane to introduce epoxy groups. It was then added to chitosan solution for covalent grafting reaction. Finally, monochloroacetic acid was added under alkaline conditions for carboxymethylation reaction. After washing and drying, a hygroscopic modifier was obtained. (2) Conductive carbon black is added to nitric acid solution for acidification and oxidation treatment; then thionyl chloride is added for acyl chloride reaction, followed by polyethylene glycol diamine for grafting reaction, and finally dodecylbenzenesulfonic acid aqueous solution, pyrrole monomer and ferric chloride for in-situ oxidative polymerization of polypyrrole. After washing and drying, an antistatic modifier is obtained. (3) Premix PET chips with polyethylene wax, then add moisture-absorbing modifier and nano zinc oxide for mixing, then add the antistatic modifier, oleamide and polyethylene glycol, and mix at high speed to obtain a blend; (4) The blend is extruded by twin screws, cooled and pelletized to obtain functional masterbatch. The masterbatch is dried and then melt-spun to obtain polyester fiber. (5) Polyester fibers are heat-stretched and shaped and cut into short fibers, and then successively processed through opening and cleaning, carding, drawing, roving, spinning and winding processes to obtain polyester fiber yarn.
[0006] In this invention, the principle for improving the moisture absorption performance of polyester fiber yarn is as follows: First, bentonite is acid-activated to remove interlayer impurity ions and increase specific surface area and pore volume. Then, γ-glycidyl etheroxypropyltrimethoxysilane is used to introduce epoxy active sites on the bentonite surface. Pre-hydrolysis is employed to uniformly anchor the silane coupling agent on the bentonite surface in monomolecular form, avoiding self-condensation and gelation. Next, the ring-opening addition reaction between epoxy groups and chitosan amino groups is used to covalently graft chitosan molecular chains onto the bentonite surface. Chitosan itself contains a large number of hydroxyl and amino groups, exhibiting excellent hydrophilicity and biocompatibility. Finally, the grafted chitosan segments are carboxymethylated to introduce a large number of carboxymethyl groups onto the molecular chain, further enhancing the hydrophilicity. Through the above chemical modification, the prepared moisture-absorbing modifier has a dual moisture-absorbing effect of layered porous structure and high-density hydrophilic groups, which can significantly improve the moisture absorption performance of polyester fibers. The principle for improving the antistatic properties of polyester fiber yarn is as follows: First, conductive carbon black is oxidized with nitric acid to introduce oxygen-containing functional groups such as carboxyl groups onto its surface. Then, thionyl chloride is used to convert the carboxyl groups into more reactive acyl chloride groups. Next, flexible polyethylene glycol segments are grafted onto the conductive carbon black surface through the amidation reaction of the acyl chloride groups with the terminal amino groups of polyethylene glycol diamine. Triethylamine is used as an acid-binding agent to neutralize the reaction byproduct HCl and improve the grafting efficiency. Finally, pyrrole monomers are oxidized and polymerized in situ on the modified conductive carbon black surface, with dodecylbenzenesulfonic acid acting as both a dopant acid and a dispersant to form a uniform polypyrrole conductive coating layer. The final antistatic modifier has a core-shell structure of conductive carbon black core-polyethylene glycol intermediate layer-polypyrrole shell, combining the intrinsic conductivity of conductive carbon black and the conjugated conductivity of polypyrrole. It can form a highly efficient conductive percolation network in the PET matrix, significantly reducing the volume resistivity of polyester fibers.
[0007] As a preference, in step (1), the mass ratio of sodium bentonite to γ-glycidoxypropyltrimethoxysilane is 1:(0.2-0.5).
[0008] As a preference, in step (1), the mass ratio of sodium bentonite to chitosan is 1:(0.3 to 1.0).
[0009] As a preferred option, in step (2), the mass ratio of conductive carbon black to thionyl chloride is 1:(2-4).
[0010] As a preference, in step (2), the mass ratio of conductive carbon black to polyethylene glycol diamine is 1:(0.3 to 0.8).
[0011] As a preference, in step (3), the mass ratio of PET chips to moisture-absorbing modifier is 140:(5-8).
[0012] As a preference, in step (3), the mass ratio of PET chips to antistatic modifier is 140:(4-6).
[0013] As a preference, in step (3), the mass ratio of PET slices to nano zinc oxide is 140:(1-2).
[0014] As a preference, in step (3), the mass ratio of PET chips to oleamide is 140:(0.5-1.5).
[0015] This invention discovered in experiments that the surface of the hygroscopic modifier contains a large number of strongly polar hydrophilic groups such as hydroxyl and carboxyl groups, while the polypyrrole layer on the surface of the antistatic modifier contains NH groups and residual oxygen-containing groups. During melt blending, strong hydrogen bonds form between the hydrophilic groups on the surface of the hygroscopic modifier and the polar groups on the surface of the antistatic modifier. This causes the two modifiers to preferentially agglomerate rather than be uniformly dispersed in the PET matrix, i.e., heterogeneous agglomeration occurs. This heterogeneous agglomeration not only destroys the ability of the antistatic modifier to form continuous conductive pathways in the matrix, significantly reducing antistatic performance, but also blocks the layered pore structure of the hygroscopic modifier, reducing its moisture absorption effect.
[0016] To address the aforementioned technical problems, this invention introduces an interface-coordinating component composed of nano-zinc oxide and oleamide. The nano-zinc oxide surface contains abundant zinc hydroxyl groups, which can coordinate with oxygen-containing groups such as carboxyl and carboxymethyl groups on the surface of the hygroscopic modifier. It preferentially occupies hydrogen-bonding active sites on the surface of the hygroscopic modifier, forming a stable coordination adsorption layer. This shields the polar groups on the surface of the hygroscopic modifier, blocking the hydrogen-bonding interaction between it and the antistatic modifier. Simultaneously, the nano-zinc oxide itself possesses semiconductor properties. After adsorbing around the hygroscopic modifier particles, it can act as a conductive bridge between adjacent antistatic modifier particles, contributing to enhanced antistatic effects. The amide groups in oleamide molecules can form selective hydrogen bonds with the NH groups of the polypyrrole layer on the surface of the antistatic modifier, preferentially coating the surface of the antistatic modifier particles. At the same time, the octadecyl long-chain olefin segments in oleamide molecules have good hydrophobicity and thermoplasticity, and are liquid at the melt processing temperature. They can form a fluid lubricating film on the surface of the antistatic modifier particles, which not only prevents direct contact between the antistatic modifier and the hygroscopic modifier, but also reduces the tendency of the antistatic modifier particles to agglomerate, promoting their uniform dispersion in the PET matrix and the formation of a conductive network.
[0017] The synergistic mechanism of nano-zinc oxide and oleamide is as follows: nano-zinc oxide blocks the polar sites on the surface of the hygroscopic modifier through coordination, while oleamide encapsulates the antistatic modifier particles through selective hydrogen bonds and hydrophobic long chains. Both simultaneously sever the heterogeneous aggregation motive force between the two fillers from the hygroscopic modifier end and the antistatic modifier end, respectively. When nano-zinc oxide is used alone, although it can shield the polar sites of the hygroscopic modifier, the antistatic modifier may still fail to form an effective conductive network due to its own aggregation. When oleamide is used alone, although it can improve the dispersibility of the antistatic modifier, the exposed polar groups on the surface of the hygroscopic modifier will still attract nearby antistatic modifiers. Only when both are used together can the heterogeneous aggregation motive force be eliminated from both ends simultaneously, achieving independent and uniform dispersion of the two functional fillers in the PET matrix, thus enabling polyester fibers to possess both excellent hygroscopic and antistatic properties.
[0018] A polyester fiber yarn is prepared by the method described above.
[0019] Compared with the prior art, the beneficial effects of the present invention are: 1. By adding a moisture-absorbing modifier that combines a layered porous physical structure with high-density hydrophilic groups of carboxymethyl / amino / hydroxyl groups to polyester fibers, the moisture absorption properties of polyester fibers are significantly improved.
[0020] 2. By preparing an antistatic modifier consisting of a conductive carbon black core, a PEG intermediate layer, and a polypyrrole outer shell, a highly efficient conductive network is formed in the fiber, significantly improving the antistatic properties of polyester.
[0021] 3. By coordinating and shielding the polar sites of the moisture-absorbing modifier with nano zinc oxide and selectively coating the antistatic modifier with oleamide, the heterogeneous aggregation driven by hydrogen bonds is bidirectionally interrupted, ensuring that the two functional fillers are independently and uniformly dispersed, thereby achieving a simultaneous improvement in moisture absorption and antistatic properties. Attached Figure Description
[0022] Figure 1 This is a low-magnification SEM image of the polyester fiber yarn prepared in Example 1 of the present invention.
[0023] Figure 2 This is a medium-magnification SEM image of the polyester fiber yarn prepared in Example 1 of the present invention.
[0024] Figure 3 This is a high-magnification SEM image of the polyester fiber yarn prepared in Example 1 of the present invention.
[0025] Figure 4 The image shows the XRD pattern of the polyester fiber yarn prepared in Example 1 of this invention. Detailed Implementation
[0026] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0027] Example 1 A method for preparing polyester fiber yarn includes the following steps: Step 1: Add 10.0g of sodium-based bentonite with a particle size of 3-8μm to 200mL of 25% hydrochloric acid solution, stir at 60℃ for 2h, filter, wash with deionized water until the pH of the filtrate is 6.5-7.0, dry in a 100℃ forced-air drying oven for 3h, grind through a 200-mesh sieve to obtain acid-activated bentonite; The acid-activated bentonite obtained above was dispersed in 80 mL of anhydrous toluene. Separately, 4 g of γ-glycidyl etheroxypropyltrimethoxysilane (KH-560) was mixed with 0.7 g of deionized water and 0.5 g of glacial acetic acid. The mixture was stirred at room temperature for 30 min to complete the pre-hydrolysis. The pre-hydrolyzed solution was diluted with 10 mL of toluene and added dropwise to the bentonite dispersion over 20 min. The mixture was refluxed and stirred at 110 °C for 6 h. After filtration, the bentonite was washed three times with anhydrous ethanol and dried under vacuum at 70 °C for 8 h to obtain epoxy-functionalized bentonite. 80g of chitosan (90% degree of deacetylation, 200,000 molecular weight) was dissolved in 350mL of 2% acetic acid aqueous solution. The pH was adjusted to 5.8 with 0.1mol / L NaOH solution. 8.0g of epoxy-functionalized bentonite was added to the chitosan solution. The mixture was stirred and reacted at 60℃ under nitrogen protection for 8h. After filtration, the mixture was washed three times each with deionized water and anhydrous ethanol, and then dried under vacuum at 60℃ for 12h to obtain chitosan-grafted bentonite. 5.0 g of chitosan-grafted bentonite was dispersed in 100 mL of deionized water, and 20 mL of 12% NaOH solution was added for alkali activation for 30 min. Then, 3.0 g of monochloroacetic acid (dissolved in 10 mL of deionized water) was added, and the mixture was stirred at 60 °C for 4 h. After filtration and washing until neutral, the mixture was vacuum dried at 55 °C for 10 h to obtain the hygroscopic modifier.
[0028] Step 2: Take 10.0g of particles with a diameter of 30-50nm and a specific surface area of 150m². 2 / g of conductive carbon black was added to 200mL of 45% nitric acid solution, stirred at room temperature for 30min to allow it to be wetted and dispersed, and then oxidized at 70℃ for 3h. After dilution, it was filtered, washed with deionized water until the pH of the filtrate was 6.0-6.5, and then vacuum dried at 90℃ for 8h to obtain oxidized conductive carbon black. 8.0 g of oxidized conductive carbon black was dispersed in 100 mL of anhydrous toluene, 3 drops of anhydrous DMF were added as a catalyst, and then 35 g of thionyl chloride was added. The mixture was refluxed and stirred at 80 °C for 4 h under nitrogen protection. Excess solvent was removed by vacuum distillation at 75 °C to obtain acyl chloride conductive carbon black. 6.0 g of acyl chloride conductive carbon black was dispersed in 80 mL of anhydrous DMF. Under nitrogen protection, 7 g of polyethylene glycol diamine with a molecular weight of 1000 and 1.5 g of anhydrous triethylamine were dissolved in 20 mL of anhydrous DMF and added dropwise to the reaction system over 30 min. The reaction was stirred at 50 °C for 6 h, filtered, washed twice with anhydrous DMF and three times with anhydrous ethanol, and dried under vacuum at 50 °C for 10 h to obtain PEG-grafted conductive carbon black. 5.0 g of PEG-grafted conductive carbon black was dispersed in 200 mL of 4% (w / w) dodecylbenzenesulfonic acid aqueous solution and ultrasonically dispersed for 30 min. 4.0 g of freshly distilled pyrrole monomer was added under 0℃ ice bath conditions, and the mixture was stirred for 20 min to allow adsorption equilibrium to be reached. 19.5 g of anhydrous FeCl3 was dissolved in 50 mL of deionized water and slowly added dropwise to the reaction system over 60 min. The mixture was stirred and polymerized at 0℃ for 8 h. After filtration, the mixture was washed 5 times with deionized water, once with 0.1 mol / L dilute hydrochloric acid, 3 times with deionized water, and twice with anhydrous ethanol. The mixture was then vacuum dried at 50℃ for 12 h to obtain the antistatic modifier.
[0029] Step 3: Add the materials to the high-speed mixer in the following order: First, add 140.0g of PET chips (vacuum pre-dried at 130℃ for 6h, moisture content <30ppm) and 0.8g of polyethylene wax, and premix at 400r / min for 2min; then add 7g of hygroscopic modifier and 1.8g of nano zinc oxide (particle size 30-60nm), and stir at 400r / min for 3min to ensure that the nano zinc oxide and hygroscopic modifier are in full contact for pre-adsorption; finally, add 5.5g of antistatic modifier, 1.2g of oleamide and 0.6g of polyethylene glycol, and stir at 400r / min for 3min to ensure that the oleamide and antistatic modifier are in full contact for pre-coating; after all the materials are added, intermittently mix at 700r / min for 5min to obtain the blend.
[0030] Step 4: Add the blend to a co-rotating twin-screw extruder (screw diameter 25mm, L / D=40:1) for extrusion granulation. The screw speed is 120r / min, and the temperatures of each section are 240℃ / 250℃ / 255℃ / 260℃ / 265℃ / 260℃. The extruded material is cooled in a water bath (water temperature 30℃) and granulated to obtain functional masterbatch. After drying the masterbatch under vacuum at 120℃ for 4 hours, it is added to a melt spinning machine for spinning. The spinning temperature is 265℃, the screw speed is 400r / min, the winding speed is 3000m / min, the spinneret orifice diameter is 0.25mm and the number of orifices is 24, the side blowing temperature is 22℃ and the wind speed is 0.5m / s to obtain polyester fiber nascent yarn.
[0031] Step 5: The nascent polyester fiber is hot-stretched and set using a drawing machine (stretching temperature 85℃, stretch ratio 3.5 times, setting temperature 130℃), and then fed into a cutting machine to cut into short fibers with a length of 35mm. The short fibers are then sequentially processed through opening and cleaning (beater speed 900r / min), carding (cylinder speed 350r / min), drawing (two merging, 8 fibers per sliver, pressure roller speed 300r / min), roving (twist 45 twists / m), spinning (twist 400 twists / m, spindle speed 12000r / min), and winding (winding tension 3cN / tex, winding speed 900r / min) processes to finally obtain polyester fiber yarn.
[0032] Example 2 A method for preparing polyester fiber yarn includes the following steps: Step 1: Add 10.0g of sodium-based bentonite with a particle size of 3-8μm to 200mL of 25% hydrochloric acid solution, stir at 60℃ for 2h, filter, wash with deionized water until the pH of the filtrate is 6.5-7.0, dry in a 100℃ forced-air drying oven for 3h, grind through a 200-mesh sieve to obtain acid-activated bentonite; The acid-activated bentonite obtained above was dispersed in 80 mL of anhydrous toluene. Separately, 3 g of γ-glycidyl etheroxypropyltrimethoxysilane (KH-560) was mixed with 0.7 g of deionized water and 0.5 g of glacial acetic acid. The mixture was stirred at room temperature for 30 min to complete the pre-hydrolysis. The pre-hydrolyzed solution was diluted with 10 mL of toluene and added dropwise to the bentonite dispersion over 20 min. The mixture was refluxed and stirred at 110 °C for 6 h. After filtration, the bentonite was washed three times with anhydrous ethanol and dried under vacuum at 70 °C for 8 h to obtain epoxy-functionalized bentonite. 5g of chitosan (90% degree of deacetylation, 200,000 molecular weight) was dissolved in 350mL of 2% acetic acid aqueous solution. The pH was adjusted to 5.8 with 0.1mol / L NaOH solution. 8.0g of epoxy-functionalized bentonite was added to the chitosan solution. The mixture was stirred and reacted at 60℃ under nitrogen protection for 8h. After filtration, the mixture was washed three times each with deionized water and anhydrous ethanol, and then dried under vacuum at 60℃ for 12h to obtain chitosan-grafted bentonite. 5.0 g of chitosan-grafted bentonite was dispersed in 100 mL of deionized water, and 20 mL of 12% NaOH solution was added for alkali activation for 30 min. Then, 3.0 g of monochloroacetic acid (dissolved in 10 mL of deionized water) was added, and the mixture was stirred at 60 °C for 4 h. After filtration and washing until neutral, the mixture was vacuum dried at 55 °C for 10 h to obtain the hygroscopic modifier.
[0033] Step 2: Take 10.0g of particles with a diameter of 30-50nm and a specific surface area of 150m². 2 / g of conductive carbon black was added to 200mL of 45% nitric acid solution, stirred at room temperature for 30min to allow it to be wetted and dispersed, and then oxidized at 70℃ for 3h. After dilution, it was filtered, washed with deionized water until the pH of the filtrate was 6.0-6.5, and then vacuum dried at 90℃ for 8h to obtain oxidized conductive carbon black. 8.0 g of oxidized conductive carbon black was dispersed in 100 mL of anhydrous toluene, 3 drops of anhydrous DMF were added as a catalyst, and then 25 g of thionyl chloride was added. The mixture was refluxed and stirred at 80 °C for 4 h under nitrogen protection. Excess solvent was removed by vacuum distillation at 75 °C to obtain acyl chloride conductive carbon black. 6.0 g of acyl chloride conductive carbon black was dispersed in 80 mL of anhydrous DMF. Under nitrogen protection, 5 g of polyethylene glycol diamine with a molecular weight of 1000 and 1.5 g of anhydrous triethylamine were dissolved in 20 mL of anhydrous DMF and added dropwise to the reaction system over 30 min. The reaction was stirred at 50 °C for 6 h, filtered, washed twice with anhydrous DMF and three times with anhydrous ethanol, and dried under vacuum at 50 °C for 10 h to obtain PEG-grafted conductive carbon black. 5.0 g of PEG-grafted conductive carbon black was dispersed in 200 mL of 4% (w / w) dodecylbenzenesulfonic acid aqueous solution and ultrasonically dispersed for 30 min. 4.0 g of freshly distilled pyrrole monomer was added under 0℃ ice bath conditions, and the mixture was stirred for 20 min to allow adsorption equilibrium to be reached. 19.5 g of anhydrous FeCl3 was dissolved in 50 mL of deionized water and slowly added dropwise to the reaction system over 60 min. The mixture was stirred and polymerized at 0℃ for 8 h. After filtration, the mixture was washed 5 times with deionized water, once with 0.1 mol / L dilute hydrochloric acid, 3 times with deionized water, and twice with anhydrous ethanol. The mixture was then vacuum dried at 50℃ for 12 h to obtain the antistatic modifier.
[0034] Step 3: Add the materials to the high-speed mixer in the following order: First, add 140.0g of PET chips (vacuum pre-dried at 130℃ for 6h, moisture content <30ppm) and 0.8g of polyethylene wax, and premix at 400r / min for 2min; then add 6g of hygroscopic modifier and 1.2g of nano zinc oxide (particle size 30-60nm), and stir at 400r / min for 3min to ensure that the nano zinc oxide and hygroscopic modifier are fully in contact and pre-adsorbed; finally, add 4.5g of antistatic modifier, 0.8g of oleamide and 0.6g of polyethylene glycol, and stir at 400r / min for 3min to ensure that the oleamide and antistatic modifier are fully in contact and pre-coated; after all the materials are added, intermittently mix at 700r / min for 5min to obtain the blend.
[0035] Step 4: Add the blend to a co-rotating twin-screw extruder (screw diameter 25mm, L / D=40:1) for extrusion granulation. The screw speed is 120r / min, and the temperatures of each section are 240℃ / 250℃ / 255℃ / 260℃ / 265℃ / 260℃. The extruded material is cooled in a water bath (water temperature 30℃) and granulated to obtain functional masterbatch. After drying the masterbatch under vacuum at 120℃ for 4 hours, it is added to a melt spinning machine for spinning. The spinning temperature is 265℃, the screw speed is 400r / min, the winding speed is 3000m / min, the spinneret orifice diameter is 0.25mm and the number of orifices is 24, the side blowing temperature is 22℃ and the wind speed is 0.5m / s to obtain polyester fiber nascent yarn.
[0036] Step 5: The nascent polyester fiber is hot-stretched and set using a drawing machine (stretching temperature 85℃, stretch ratio 3.5 times, setting temperature 130℃), and then fed into a cutting machine to cut into short fibers with a length of 35mm. The short fibers are then sequentially processed through opening and cleaning (beater speed 900r / min), carding (cylinder speed 350r / min), drawing (two merging, 8 fibers per sliver, pressure roller speed 300r / min), roving (twist 45 twists / m), spinning (twist 400 twists / m, spindle speed 12000r / min), and winding (winding tension 3cN / tex, winding speed 900r / min) processes to finally obtain polyester fiber yarn.
[0037] Example 3 A method for preparing polyester fiber yarn includes the following steps: Step 1: Add 10.0g of sodium-based bentonite with a particle size of 3-8μm to 200mL of 25% hydrochloric acid solution, stir at 60℃ for 2h, filter, wash with deionized water until the pH of the filtrate is 6.5-7.0, dry in a 100℃ forced-air drying oven for 3h, grind through a 200-mesh sieve to obtain acid-activated bentonite; The acid-activated bentonite obtained above was dispersed in 80 mL of anhydrous toluene. Separately, 3.5 g of γ-glycidyl etheroxypropyltrimethoxysilane (KH-560) was mixed with 0.7 g of deionized water and 0.5 g of glacial acetic acid. The mixture was stirred at room temperature for 30 min to complete the pre-hydrolysis. The pre-hydrolyzed solution was diluted with 10 mL of toluene and added dropwise to the bentonite dispersion over 20 min. The mixture was refluxed and stirred at 110 °C for 6 h. After filtration, the bentonite was washed three times with anhydrous ethanol and dried under vacuum at 70 °C for 8 h to obtain epoxy-functionalized bentonite. 6 g of chitosan (90% degree of deacetylation, 200,000 molecular weight) was dissolved in 350 mL of 2% acetic acid aqueous solution. The pH was adjusted to 5.8 with 0.1 mol / L NaOH solution. 8.0 g of epoxy-functionalized bentonite was added to the chitosan solution. The mixture was stirred and reacted at 60 °C for 8 h under nitrogen protection. After filtration, the mixture was washed three times each with deionized water and anhydrous ethanol, and then dried under vacuum at 60 °C for 12 h to obtain chitosan-grafted bentonite. 5.0 g of chitosan-grafted bentonite was dispersed in 100 mL of deionized water, and 20 mL of 12% NaOH solution was added for alkali activation for 30 min. Then, 3.0 g of monochloroacetic acid (dissolved in 10 mL of deionized water) was added, and the mixture was stirred at 60 °C for 4 h. After filtration and washing until neutral, the mixture was vacuum dried at 55 °C for 10 h to obtain the hygroscopic modifier.
[0038] Step 2: Take 10.0g of particles with a diameter of 30-50nm and a specific surface area of 150m². 2 / g of conductive carbon black was added to 200mL of 45% nitric acid solution, stirred at room temperature for 30min to allow it to be wetted and dispersed, and then oxidized at 70℃ for 3h. After dilution, it was filtered, washed with deionized water until the pH of the filtrate was 6.0-6.5, and then vacuum dried at 90℃ for 8h to obtain oxidized conductive carbon black. 8.0 g of oxidized conductive carbon black was dispersed in 100 mL of anhydrous toluene, 3 drops of anhydrous DMF were added as a catalyst, and then 30 g of thionyl chloride was added. The mixture was refluxed and stirred at 80 °C for 4 h under nitrogen protection. Excess solvent was removed by vacuum distillation at 75 °C to obtain acyl chloride conductive carbon black. 6.0 g of acyl chloride conductive carbon black was dispersed in 80 mL of anhydrous DMF. Under nitrogen protection, 5 g of polyethylene glycol diamine with a molecular weight of 1000 and 1.5 g of anhydrous triethylamine were dissolved in 20 mL of anhydrous DMF and added dropwise to the reaction system over 30 min. The reaction was stirred at 50 °C for 6 h, filtered, washed twice with anhydrous DMF and three times with anhydrous ethanol, and dried under vacuum at 50 °C for 10 h to obtain PEG-grafted conductive carbon black. 5.0 g of PEG-grafted conductive carbon black was dispersed in 200 mL of 4% (w / w) dodecylbenzenesulfonic acid aqueous solution and ultrasonically dispersed for 30 min. 4.0 g of freshly distilled pyrrole monomer was added under 0℃ ice bath conditions, and the mixture was stirred for 20 min to allow adsorption equilibrium to be reached. 19.5 g of anhydrous FeCl3 was dissolved in 50 mL of deionized water and slowly added dropwise to the reaction system over 60 min. The mixture was stirred and polymerized at 0℃ for 8 h. After filtration, the mixture was washed 5 times with deionized water, once with 0.1 mol / L dilute hydrochloric acid, 3 times with deionized water, and twice with anhydrous ethanol. The mixture was then vacuum dried at 50℃ for 12 h to obtain the antistatic modifier.
[0039] Step 3: Add the materials to the high-speed mixer in the following order: First, add 140.0g of PET chips (vacuum pre-dried at 130℃ for 6h, moisture content <30ppm) and 0.8g of polyethylene wax, and premix at 400r / min for 2min; then add 6.5g of hygroscopic modifier and 1.5g of nano zinc oxide (particle size 30-60nm), and stir at 400r / min for 3min to ensure that the nano zinc oxide and hygroscopic modifier are fully in contact and pre-adsorbed; finally, add 5g of antistatic modifier, 1.0g of oleamide and 0.6g of polyethylene glycol, and stir at 400r / min for 3min to ensure that the oleamide and antistatic modifier are fully in contact and pre-coated; after all the materials are added, intermittently mix at 700r / min for 5min to obtain the blend.
[0040] Step 4: Add the blend to a co-rotating twin-screw extruder (screw diameter 25mm, L / D=40:1) for extrusion granulation. The screw speed is 120r / min, and the temperatures of each section are 240℃ / 250℃ / 255℃ / 260℃ / 265℃ / 260℃. The extruded material is cooled in a water bath (water temperature 30℃) and granulated to obtain functional masterbatch. After drying the masterbatch under vacuum at 120℃ for 4 hours, it is added to a melt spinning machine for spinning. The spinning temperature is 265℃, the screw speed is 400r / min, the winding speed is 3000m / min, the spinneret orifice diameter is 0.25mm and the number of orifices is 24, the side blowing temperature is 22℃ and the wind speed is 0.5m / s to obtain polyester fiber nascent yarn.
[0041] Step 5: The nascent polyester fiber is hot-stretched and set using a drawing machine (stretching temperature 85℃, stretch ratio 3.5 times, setting temperature 130℃), and then fed into a cutting machine to cut into short fibers with a length of 35mm. The short fibers are then sequentially processed through opening and cleaning (beater speed 900r / min), carding (cylinder speed 350r / min), drawing (two merging, 8 fibers per sliver, pressure roller speed 300r / min), roving (twist 45 twists / m), spinning (twist 400 twists / m, spindle speed 12000r / min), and winding (winding tension 3cN / tex, winding speed 900r / min) processes to finally obtain polyester fiber yarn.
[0042] Example 4 A method for preparing polyester fiber yarn includes the following steps: Step 1: Add 10.0g of sodium-based bentonite with a particle size of 3-8μm to 200mL of 25% hydrochloric acid solution, stir at 60℃ for 2h, filter, wash with deionized water until the pH of the filtrate is 6.5-7.0, dry in a 100℃ forced-air drying oven for 3h, grind through a 200-mesh sieve to obtain acid-activated bentonite; The acid-activated bentonite obtained above was dispersed in 80 mL of anhydrous toluene. Separately, 5 g of γ-glycidyl etheroxypropyltrimethoxysilane (KH-560) was mixed with 0.7 g of deionized water and 0.5 g of glacial acetic acid. The mixture was stirred at room temperature for 30 min to complete the pre-hydrolysis. The pre-hydrolyzed solution was diluted with 10 mL of toluene and added dropwise to the bentonite dispersion over 20 min. The mixture was refluxed and stirred at 110 °C for 6 h. After filtration, the bentonite was washed three times with anhydrous ethanol and dried under vacuum at 70 °C for 8 h to obtain epoxy-functionalized bentonite. 10g of chitosan (90% degree of deacetylation, 200,000 molecular weight) was dissolved in 350mL of 2% acetic acid aqueous solution. The pH was adjusted to 5.8 with 0.1mol / L NaOH solution. 8.0g of epoxy-functionalized bentonite was added to the chitosan solution. The mixture was stirred and reacted at 60℃ under nitrogen protection for 8h. After filtration, the mixture was washed three times each with deionized water and anhydrous ethanol, and then dried under vacuum at 60℃ for 12h to obtain chitosan-grafted bentonite. 5.0 g of chitosan-grafted bentonite was dispersed in 100 mL of deionized water, and 20 mL of 12% NaOH solution was added for alkali activation for 30 min. Then, 3.0 g of monochloroacetic acid (dissolved in 10 mL of deionized water) was added, and the mixture was stirred at 60 °C for 4 h. After filtration and washing until neutral, the mixture was vacuum dried at 55 °C for 10 h to obtain the hygroscopic modifier.
[0043] Step 2: Take 10.0g of particles with a diameter of 30-50nm and a specific surface area of 150m². 2 / g of conductive carbon black was added to 200mL of 45% nitric acid solution, stirred at room temperature for 30min to allow it to be wetted and dispersed, and then oxidized at 70℃ for 3h. After dilution, it was filtered, washed with deionized water until the pH of the filtrate was 6.0-6.5, and then vacuum dried at 90℃ for 8h to obtain oxidized conductive carbon black. 8.0 g of oxidized conductive carbon black was dispersed in 100 mL of anhydrous toluene, 3 drops of anhydrous DMF were added as a catalyst, and then 40 g of thionyl chloride was added. The mixture was refluxed and stirred at 80 °C for 4 h under nitrogen protection. Excess solvent was removed by vacuum distillation at 75 °C to obtain acyl chloride conductive carbon black. 6.0 g of acyl chloride conductive carbon black was dispersed in 80 mL of anhydrous DMF. Under nitrogen protection, 8 g of polyethylene glycol diamine with a molecular weight of 1000 and 1.5 g of anhydrous triethylamine were dissolved in 20 mL of anhydrous DMF and added dropwise to the reaction system over 30 min. The reaction was stirred at 50 °C for 6 h, filtered, washed twice with anhydrous DMF and three times with anhydrous ethanol, and dried under vacuum at 50 °C for 10 h to obtain PEG-grafted conductive carbon black. 5.0 g of PEG-grafted conductive carbon black was dispersed in 200 mL of 4% (w / w) dodecylbenzenesulfonic acid aqueous solution and ultrasonically dispersed for 30 min. 4.0 g of freshly distilled pyrrole monomer was added under 0℃ ice bath conditions, and the mixture was stirred for 20 min to allow adsorption equilibrium to be reached. 19.5 g of anhydrous FeCl3 was dissolved in 50 mL of deionized water and slowly added dropwise to the reaction system over 60 min. The mixture was stirred and polymerized at 0℃ for 8 h. After filtration, the mixture was washed 5 times with deionized water, once with 0.1 mol / L dilute hydrochloric acid, 3 times with deionized water, and twice with anhydrous ethanol. The mixture was then vacuum dried at 50℃ for 12 h to obtain the antistatic modifier.
[0044] Step 3: Add the materials to the high-speed mixer in the following order: First, add 140.0g of PET chips (vacuum pre-dried at 130℃ for 6h, moisture content <30ppm) and 0.8g of polyethylene wax, and premix at 400r / min for 2min; then add 8g of hygroscopic modifier and 2g of nano zinc oxide (particle size 30-60nm), and stir at 400r / min for 3min to ensure that the nano zinc oxide and hygroscopic modifier are fully in contact to achieve pre-adsorption; finally, add 6g of antistatic modifier, 1.5g of oleamide and 0.6g of polyethylene glycol, and stir at 400r / min for 3min to ensure that the oleamide and antistatic modifier are fully in contact to achieve pre-coating; after all the materials are added, intermittently mix at 700r / min for 5min to obtain the blend.
[0045] Step 4: Add the blend to a co-rotating twin-screw extruder (screw diameter 25mm, L / D=40:1) for extrusion granulation. The screw speed is 120r / min, and the temperatures of each section are 240℃ / 250℃ / 255℃ / 260℃ / 265℃ / 260℃. The extruded material is cooled in a water bath (water temperature 30℃) and granulated to obtain functional masterbatch. After drying the masterbatch under vacuum at 120℃ for 4 hours, it is added to a melt spinning machine for spinning. The spinning temperature is 265℃, the screw speed is 400r / min, the winding speed is 3000m / min, the spinneret orifice diameter is 0.25mm and the number of orifices is 24, the side blowing temperature is 22℃ and the wind speed is 0.5m / s to obtain polyester fiber nascent yarn.
[0046] Step 5: The nascent polyester fiber is hot-stretched and set using a drawing machine (stretching temperature 85℃, stretch ratio 3.5 times, setting temperature 130℃), and then fed into a cutting machine to cut into short fibers with a length of 35mm. The short fibers are then sequentially processed through opening and cleaning (beater speed 900r / min), carding (cylinder speed 350r / min), drawing (two merging, 8 fibers per sliver, pressure roller speed 300r / min), roving (twist 45 twists / m), spinning (twist 400 twists / m, spindle speed 12000r / min), and winding (winding tension 3cN / tex, winding speed 900r / min) processes to finally obtain polyester fiber yarn.
[0047] Example 5 A method for preparing polyester fiber yarn includes the following steps: Step 1: Add 10.0g of sodium-based bentonite with a particle size of 3-8μm to 200mL of 25% hydrochloric acid solution, stir at 60℃ for 2h, filter, wash with deionized water until the pH of the filtrate is 6.5-7.0, dry in a 100℃ forced-air drying oven for 3h, grind through a 200-mesh sieve to obtain acid-activated bentonite; The acid-activated bentonite obtained above was dispersed in 80 mL of anhydrous toluene. Separately, 2 g of γ-glycidyl etheroxypropyltrimethoxysilane (KH-560) was mixed with 0.7 g of deionized water and 0.5 g of glacial acetic acid. The mixture was stirred at room temperature for 30 min to complete the pre-hydrolysis. The pre-hydrolyzed solution was diluted with 10 mL of toluene and added dropwise to the bentonite dispersion over 20 min. The mixture was refluxed and stirred at 110 °C for 6 h. After filtration, the bentonite was washed three times with anhydrous ethanol and dried under vacuum at 70 °C for 8 h to obtain epoxy-functionalized bentonite. 3g of chitosan (90% degree of deacetylation, 200,000 molecular weight) was dissolved in 350mL of 2% acetic acid aqueous solution. The pH was adjusted to 5.8 with 0.1mol / L NaOH solution. 8.0g of epoxy-functionalized bentonite was added to the chitosan solution. The mixture was stirred and reacted at 60℃ under nitrogen protection for 8h. After filtration, the mixture was washed three times each with deionized water and anhydrous ethanol, and then dried under vacuum at 60℃ for 12h to obtain chitosan-grafted bentonite. 5.0 g of chitosan-grafted bentonite was dispersed in 100 mL of deionized water, and 20 mL of 12% NaOH solution was added for alkali activation for 30 min. Then, 3.0 g of monochloroacetic acid (dissolved in 10 mL of deionized water) was added, and the mixture was stirred at 60 °C for 4 h. After filtration and washing until neutral, the mixture was vacuum dried at 55 °C for 10 h to obtain the hygroscopic modifier.
[0048] Step 2: Take 10.0g of particles with a diameter of 30-50nm and a specific surface area of 150m². 2 / g of conductive carbon black was added to 200mL of 45% nitric acid solution, stirred at room temperature for 30min to allow it to be wetted and dispersed, and then oxidized at 70℃ for 3h. After dilution, it was filtered, washed with deionized water until the pH of the filtrate was 6.0-6.5, and then vacuum dried at 90℃ for 8h to obtain oxidized conductive carbon black. 8.0 g of oxidized conductive carbon black was dispersed in 100 mL of anhydrous toluene, 3 drops of anhydrous DMF were added as a catalyst, and then 20 g of thionyl chloride was added. The mixture was refluxed and stirred at 80 °C for 4 h under nitrogen protection. Excess solvent was removed by vacuum distillation at 75 °C to obtain acyl chloride conductive carbon black. 6.0 g of acyl chloride conductive carbon black was dispersed in 80 mL of anhydrous DMF. Under nitrogen protection, 3 g of polyethylene glycol diamine with a molecular weight of 1000 and 1.5 g of anhydrous triethylamine were dissolved in 20 mL of anhydrous DMF and added dropwise to the reaction system over 30 min. The reaction was stirred at 50 °C for 6 h, filtered, washed twice with anhydrous DMF and three times with anhydrous ethanol, and dried under vacuum at 50 °C for 10 h to obtain PEG-grafted conductive carbon black. 5.0 g of PEG-grafted conductive carbon black was dispersed in 200 mL of 4% (w / w) dodecylbenzenesulfonic acid aqueous solution and ultrasonically dispersed for 30 min. 4.0 g of freshly distilled pyrrole monomer was added under 0℃ ice bath conditions, and the mixture was stirred for 20 min to allow adsorption equilibrium to be reached. 19.5 g of anhydrous FeCl3 was dissolved in 50 mL of deionized water and slowly added dropwise to the reaction system over 60 min. The mixture was stirred and polymerized at 0℃ for 8 h. After filtration, the mixture was washed 5 times with deionized water, once with 0.1 mol / L dilute hydrochloric acid, 3 times with deionized water, and twice with anhydrous ethanol. The mixture was then vacuum dried at 50℃ for 12 h to obtain the antistatic modifier.
[0049] Step 3: Add the materials to the high-speed mixer in the following order: First, add 140.0g of PET chips (vacuum pre-dried at 130℃ for 6h, moisture content <30ppm) and 0.8g of polyethylene wax, and premix at 400r / min for 2min; then add 5g of hygroscopic modifier and 1g of nano zinc oxide (particle size 30-60nm), and stir at 400r / min for 3min to ensure that the nano zinc oxide and hygroscopic modifier are fully in contact and pre-adsorbed; finally, add 4g of antistatic modifier, 0.5g of oleamide and 0.6g of polyethylene glycol, and stir at 400r / min for 3min to ensure that the oleamide and antistatic modifier are fully in contact and pre-coated; after all the materials are added, intermittently mix at 700r / min for 5min to obtain the blend.
[0050] Step 4: Add the blend to a co-rotating twin-screw extruder (screw diameter 25mm, L / D=40:1) for extrusion granulation. The screw speed is 120r / min, and the temperatures of each section are 240℃ / 250℃ / 255℃ / 260℃ / 265℃ / 260℃. The extruded material is cooled in a water bath (water temperature 30℃) and granulated to obtain functional masterbatch. After drying the masterbatch under vacuum at 120℃ for 4 hours, it is added to a melt spinning machine for spinning. The spinning temperature is 265℃, the screw speed is 400r / min, the winding speed is 3000m / min, the spinneret orifice diameter is 0.25mm and the number of orifices is 24, the side blowing temperature is 22℃ and the wind speed is 0.5m / s to obtain polyester fiber nascent yarn.
[0051] Step 5: The nascent polyester fiber is hot-stretched and set using a drawing machine (stretching temperature 85℃, stretch ratio 3.5 times, setting temperature 130℃), and then fed into a cutting machine to cut into short fibers with a length of 35mm. The short fibers are then sequentially processed through opening and cleaning (beater speed 900r / min), carding (cylinder speed 350r / min), drawing (two merging, 8 fibers per sliver, pressure roller speed 300r / min), roving (twist 45 twists / m), spinning (twist 400 twists / m, spindle speed 12000r / min), and winding (winding tension 3cN / tex, winding speed 900r / min) processes to finally obtain polyester fiber yarn.
[0052] Comparative Example 1: Pure PET polyester fiber yarn, without any modifiers or interface coordinating components, only PET chips, lubricants and dispersants were added, and the remaining spinning and spinning conditions were the same as in Example 1.
[0053] Comparative Example 2: No antistatic modifier was added during the preparation of polyester fiber yarn, and the other conditions were the same as in Example 1.
[0054] Comparative Example 3: No moisture-absorbing modifier was added during the preparation of polyester fiber yarn, and the other conditions were the same as in Example 1.
[0055] Comparative Example 4: No nano zinc oxide and oleamide were added during the preparation of polyester fiber yarn, and the other conditions were the same as in Example 1.
[0056] Comparative Example 5: No nano zinc oxide was added during the preparation of polyester fiber yarn, and the other conditions were the same as in Example 1.
[0057] Comparative Example 6: No oleamide was added during the preparation of polyester fiber yarn, and the other conditions were the same as in Example 1.
[0058] Performance testing: The polyester fiber yarns prepared in Examples 1-5 and Comparative Examples 1-6 of this invention were made into samples that met the test specifications, and the following performance tests were performed respectively: 1. Moisture absorption performance test: According to GB / T 6503-2017 "Test method for moisture regain of chemical fibers", the samples were equilibrated for 24 hours under standard atmospheric conditions of 20±2℃ and 65±3% relative humidity. The moisture regain (%) of the samples was determined by oven drying method. Each group of samples was tested in parallel 5 times and the arithmetic mean was taken.
[0059] 2. Antistatic performance test: According to GB / T 12703.4-2010 "Evaluation of electrostatic properties of textiles - Part 4: resistivity", the samples were pretreated for 24 hours at a temperature of 20±2℃ and a relative humidity of 35±5%. The surface resistivity (Ω) of the samples was tested using a high resistance meter (applied voltage 100V). Each group of samples was tested in parallel 3 times, and the arithmetic mean was taken.
[0060] 3. Tensile strength test: All yarn samples were conditioned in a standard atmospheric environment (20±2℃, 65±3%RH) for more than 24 hours. The standard clamping distance was set to 500mm, the tensile speed to 450mm / min, and the pre-tension of a single yarn to (0.05±0.005)cN / dtex. The tensile strength (cN / dtex) and elongation at break (%) of the samples were tested. Each group of samples was tested in parallel 10 times, and the arithmetic mean was taken.
[0061] 4. Heat resistance stability test: Place the sample in a 150℃ forced-air drying oven for 24 hours. After taking it out, equilibrate it in a standard atmospheric environment for 4 hours. Then test the fracture strength of the sample again according to the above fracture strength test method and calculate the fracture strength retention rate (%). The formula is: fracture strength retention rate = fracture strength after high temperature treatment / initial fracture strength × 100%.
[0062] 5. Washability test: According to GB / T 8629-2017 "Home washing and drying procedures for textile testing", the samples were washed 30 times under the standard washing procedure (40℃, standard detergent, washing for 30 min). The moisture regain and surface resistivity of the samples were then tested again to evaluate the washability of the moisture absorption and antistatic properties.
[0063] The specific test results are shown in the table below: Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing polyester fiber yarn, characterized in that, Includes the following steps: (1) Sodium-based bentonite was acid-activated with hydrochloric acid solution, and then modified with γ-glycidoxypropyltrimethoxysilane to introduce epoxy groups. It was then added to chitosan solution for covalent grafting reaction. Finally, monochloroacetic acid was added under alkaline conditions for carboxymethylation reaction. After washing and drying, a hygroscopic modifier was obtained. (2) Conductive carbon black is added to nitric acid solution for acidification and oxidation treatment; then thionyl chloride is added for acyl chloride reaction, followed by polyethylene glycol diamine for grafting reaction, and finally dodecylbenzenesulfonic acid aqueous solution, pyrrole monomer and ferric chloride for in-situ oxidative polymerization of polypyrrole. After washing and drying, an antistatic modifier is obtained. (3) Premix PET chips with polyethylene wax, then add moisture-absorbing modifier and nano zinc oxide for mixing, then add the antistatic modifier, oleamide and polyethylene glycol, and mix at high speed to obtain a blend; (4) The blend is extruded by twin screws, cooled and pelletized to obtain functional masterbatch. The masterbatch is dried and then melt-spun to obtain polyester fiber. (5) Polyester fibers are heat-stretched and shaped and cut into short fibers, and then successively processed through opening and cleaning, carding, drawing, roving, spinning and winding processes to obtain polyester fiber yarn.
2. The method for preparing polyester fiber yarn according to claim 1, characterized in that, In step (1), the mass ratio of sodium bentonite to γ-glycidoxypropyltrimethoxysilane is 1:(0.2-0.5).
3. The method for preparing polyester fiber yarn according to claim 1, characterized in that, In step (1), the mass ratio of sodium bentonite to chitosan is 1:(0.3-1.0).
4. The method for preparing polyester fiber yarn according to claim 1, characterized in that, In step (2), the mass ratio of conductive carbon black to thionyl chloride is 1:(2-4).
5. The method for preparing polyester fiber yarn according to claim 1, characterized in that, In step (2), the mass ratio of conductive carbon black to polyethylene glycol diamine is 1:(0.3-0.8).
6. The method for preparing polyester fiber yarn according to claim 1, characterized in that, In step (3), the mass ratio of PET chips to moisture-absorbing modifier is 140:(5-8).
7. The method for preparing polyester fiber yarn according to claim 1, characterized in that, In step (3), the mass ratio of PET chips to antistatic modifier is 140:(4-6).
8. The method for preparing polyester fiber yarn according to claim 1, characterized in that, In step (3), the mass ratio of PET slices to nano zinc oxide is 140:(1-2).
9. The method for preparing polyester fiber yarn according to claim 1, characterized in that, In step (3), the mass ratio of PET chips to oleamide is 140:(0.5-1.5).
10. A polyester fiber yarn, characterized in that, It is prepared by the method described in any one of claims 1 to 9 above.
Citation Information
Patent Citations
Method for preparing polymer electrostatic spinning receiving net curtains
CN109097842A
Artificial turf and manufacturing method thereof
CN115748126A
